Fuzzy logic control of vehicle suspensions with dry friction nonlinearity - Sakman, LE; Guclu, R; Yagiz, N (SPRINGER INDIA, 2005)
We design and investigate the performance of fuzzy logic-controlled (FLC) active suspensions on a nonlinear vehicle model with four degrees of freedom, without Causing any degeneration in suspension working limits. Force actuators Were Mounted parallel to the suspensions. In this new approach, linear combinations of the vertical velocities of the Suspension ends and accelerations of the points of connection of the Suspension to the body have been used as input variables. The study clearly demonstrates the effectiveness of the fuzzy logic controller for active Suspension systems. Suspension working space degeneration is the most important problem in various applications. Decreasing the amplitudes of vehicle body vibrations improves ride comfort. Body bounce and pitch motion of the vehicle are presented both in time domain when travelling over a ramp-step road profile and in frequency domain. The results are compared with those Of uncontrolled systems. At the end of this study, the performance and the advantage of the Suggested approach and the improvement in ride comfort are discussed.
Keywords: fuzzy logic control; active vehicle suspension; suspension space; Engineering